Effects of Content Support and Planning Instruction on Discourse Connection in EFL Argumentative Writing - Xie, Yue; Lv, Xiaoxuan (Frontiers in Psychology, 2022)
Discourse connection is a challenging aspect of writing in a second language. This study seeks to investigate the effects of two classroom instructions on discourse connection in writing for EFL college students, focusing on their argumentative writing. Three classes were exposed to different pre-task conditions: receiving reading materials that provide content support for the writing, receiving planning instructions on effective outlining, and receiving no resources. The results showed that the instructions helped students attain better overall coherence in writing. However, noticeable differences between the two experimental groups emerged in terms of cohesion features. The reading group was found to employ more lexical cohesion devices in writing than the outline group, which indicated a heightened genre awareness. This inquiry helped us identify the reading group’s alignment with content support materials, particularly the change in stance as a factor that contributes to a higher level of lexical cohesion in writing.